Long Non-Coding RNAs SNHG7, SNHG12, and SNHG14 in Rheumatoid Arthritis: Clinical and In Silico Analysis - Michał Czerewaty; Paweł Dec; Krzysztof Safranow; Andrzej Pawlik (Current Issues in Molecular Biology, 2026)
Rheumatoid arthritis (RA) is an autoimmune disease with a complex pathogenesis. It has been shown that epigenetic modifications can influence the differentiation and function of many immune system cells involved in the pathogenesis of RA. Important epigenetic factors include non-coding RNAs, such as long non-coding RNAs (lncRNAs). Non-coding RNAs can influence numerous immune processes in RA. This study aimed to evaluate the expression of lncRNAs SNHG7, SNHG12, and SNHG14 in the synovial membranes of patients with RA and to correlate these results with selected clinical parameters of the disease. This study included 46 patients diagnosed with RA and 67 healthy individuals as the control group. The expression levels of the lncRNAs SNHG7, SNHG12, and SNHG14 in synovial membranes in patients with RA were statistically higher than those in the control group. The synovial expression of SNHG14 showed a statistically significant negative correlation with C-reactive protein values. There were no statistically significant correlations between synovial expression of SNHG7, SNHG12, and clinical parameters. The study results suggest that lncRNAs may potentially play a role in the development of RA.